Pengaruh Badan Usaha Milik Desa (BUMDes) Terhadap Kesejahteraan Masyarakat Di Desa Pajalele Kecamatan Tanasitolo Kabupaten Wajo - Yusran Yusran; Sofyan Marzuki; Ayu Ariska (Journal of Research and Development on Public Policy, 2023)
This research is motivated by the Government Program in improving the welfare of the people of Pajalele Village. One of the efforts made by the government to develop Village development is by establishing a Village-Owned Enterprise (BUMDes) by optimizing two business units namely the Savings and Loans Unit and the Tent Rental Unit so that it can improve the welfare of the people of Pajalele Village, Tanasitolo District, Wajo Regency. This study aims to examine the influence of village-owned enterprises (BUMDes) on community welfare in Pajalele Village, Tanasitolo District, Wajo Regency. This research uses quantitative research methods. The population in this study were the people of Pajalele Village who used BUMDes services totaling 126 people, the sample in this study used a probability sampling technique with a simple random sampling type while the sample size was obtained from calculations using the Slovin formula with an error rate of 10% from 56 people. The primary data source is in the form of a questionnaire. The data analysis technique used is descriptive statistical analysis, correlation analysis, coefficient of determination, simple linear regression analysis. Questionnaire measurements answered by respondents used a Likert scale which was processed using Statistical Product and Service Solution (SPSS). The results of this study indicate that village-owned enterprises (BUMDes) have a positive and significant influence on the welfare of the people in Pajalele Village, Tanasitolo District, Wajo Regency. While the value of R2 (R Square) is 0.208 which indicates that the percentage contribution of Village-Owned Enterprises (BUMDes) variables to the community welfare variable in Pajalele Village, Tanasitolo District, Wajo Regency is 20.8%.